2017
DOI: 10.17116/neiro20178125-21
|View full text |Cite
|
Sign up to set email alerts
|

The use of high-flow extracranial-intracranial artery bypass in pathology of the cerebral and brachiocephalic arteries: technical features and surgical outcomes

Abstract: Implementation of a large number of surgeries enabled improvement of the technique and clarification of the prerequisites for preoperative examination, intraoperative control, and postoperative management of patients. A low mortalits rate suggests this technique for use in clinical practice. The surgery is indicated for the treatment of giant aneurysms of the petrous, cavernous, and clinoid segments of the ICA. In the case of giant supraclinoid aneurysms, the surgery may be combined with removal of thrombotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In strokes, studies have shown benefit in candidates requiring urgent reperfusion when intra-arterial thrombolysis (ITA) is unavailable or contraindicated, with one study showing significant improvement in NIH stroke scales, neurological outcomes, and “good” outcomes (as defined by Rankin scale). [ 8 13 17 33 ] The role and benefit of surgical anastomotic intervention in Moyamoya disease are well-established, with marked benefit noted in numerous studies. [ 9 23 35 ] Furthermore, bypass technique is used in selected complex cerebral aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…In strokes, studies have shown benefit in candidates requiring urgent reperfusion when intra-arterial thrombolysis (ITA) is unavailable or contraindicated, with one study showing significant improvement in NIH stroke scales, neurological outcomes, and “good” outcomes (as defined by Rankin scale). [ 8 13 17 33 ] The role and benefit of surgical anastomotic intervention in Moyamoya disease are well-established, with marked benefit noted in numerous studies. [ 9 23 35 ] Furthermore, bypass technique is used in selected complex cerebral aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…The RA is used in neurosurgery for high-flow bypass procedures involving complex aneurysms situated between the middle cerebral artery and external carotid artery [3]. Notably, occlusion or thrombus formation within the graft can lead to severe complications [16]. Additionally, RA is commonly used in coronary artery bypass grafting, with some histological studies reported [17].…”
Section: Introductionmentioning
confidence: 99%